The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1158/0008-5472.can-14-0092
|View full text |Cite
|
Sign up to set email alerts
|

Favorable Prognostic Impact in Loss of TP53 and PIK3CA Mutations after Neoadjuvant Chemotherapy in Breast Cancer

Abstract: We investigated the loss of somatic mutations in TP53 and PIK3CA in breast cancer tissue after neoadjuvant chemotherapy (NCT) and the clinical relevance of the observed mutation profiles. Samples were derived from three cohorts: Cohort 1 consisting of 206 patients undergoing NCT with matched pre-and postchemotherapy tumor tissues; Cohort 2 consisting of 158 additional patients undergoing NCT; and Cohort 3, consisting of 81 patients undergoing chemotherapy with prechemotherapy tumor tissues. In the first cohort… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 37 publications
4
28
0
1
Order By: Relevance
“…Our PIK3CA mutation rate (23.3%) was consistent with the literature, as well as our rate of different hotspot mutations [3,14,19,[22][23][24][25][26][27][28][29][30][31][32][33][34]. Also, we confirmed significant associations of different types of PIK3CA mutations with clinicopathological and molecular characteristics.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our PIK3CA mutation rate (23.3%) was consistent with the literature, as well as our rate of different hotspot mutations [3,14,19,[22][23][24][25][26][27][28][29][30][31][32][33][34]. Also, we confirmed significant associations of different types of PIK3CA mutations with clinicopathological and molecular characteristics.…”
Section: Discussionsupporting
confidence: 91%
“…One important question is the possible effect of PIK3CA status on cancer outcome and treatment efficacy. Notably, many studies examining the prognostic significance of PIK3CA mutations in breast cancer [35] have been published, however very few included a large enough number of patients [3,14,19,[22][23][24][25][26][27][28][29][30][31][32][33][34]. Also, less than half of them [22,24,26,28,30,31,33] used data from clinical trials, thus excluding the effect of treatment heterogeneity when evaluating prognostic factors.…”
Section: Discussionmentioning
confidence: 99%
“…We performed macrodissection of tumor tissues to ensure that the percentage of tumor cells was 80% or more in all breast cancer specimens (18). Total RNA was isolated from 275 adjuvant TNBC samples, 33 paired adjacent normal breast tissues, and 82 CNB TNBC tissues using the Rneasy Plus Mini Kit (Qiagen).…”
Section: Sample Preparationmentioning
confidence: 99%
“…3B) [74,76]. Several studies showed that appearance of new mutations, undetectable in the primary tumor, can arise after neoadjuvant chemotherapy (PTEN and TP53), HER2-targeted therapies (PIK3CA), and during endocrine therapy (ESR1) for metastatic breast cancer [50][51][52][53][54][77][78][79]. Even though the relative proportion of drug-resistant subclones is generally higher in the post-treatment specimens, retreating cancers with drugs on which they previously progressed often continues to produce tumor response.…”
Section: Intratumor Genomic Heterogeneity and Implications For Treatmentmentioning
confidence: 99%